2018
DOI: 10.1002/ajh.25365
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood biomarkers of early immune reconstitution in newly diagnosed multiple myeloma

Abstract: Peripheral blood biomarkers of tumor microenvironment and immune surveillance are independent prognostic factors in multiple myeloma. The timing and prognostic impact of immune reconstitution has been studied after autologous hematopoietic stem cell transplantation, less is known about its significance in newly diagnosed multiple myeloma. We studied absolute lymphocyte (ALC) and absolute monocyte (AMC) counts at the time of treatment initiation and 1 month thereafter in 771 newly diagnosed patients. Two hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
(34 reference statements)
1
19
1
Order By: Relevance
“…The early immune reconstitution of multiple myeloma is defined as the recovery of absolute lymphocyte count and monocyte counts to normal reference range 1 month after treatment initiation ( 22 ). Therefore, we analyzed the effect of NMLR on early immune reconstitution in MM patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The early immune reconstitution of multiple myeloma is defined as the recovery of absolute lymphocyte count and monocyte counts to normal reference range 1 month after treatment initiation ( 22 ). Therefore, we analyzed the effect of NMLR on early immune reconstitution in MM patients.…”
Section: Resultsmentioning
confidence: 99%
“…Another important finding of this study was that the proportion of patients with high NMLR who achieved early immune reconstitution after 1 month of treatment with BCD was significantly smaller than that of patients with low NMLR, and the NMLR value at diagnosis of patients who achieved early immune reconstitution was significantly lower than those without early immune reconstitution. These results suggested that the treatment based on bortezomib may not overcome the effect of immunosuppressive microenvironment on the poor prognosis of MM, which may be related to the mechanism of bortezomib ( 14 , 22 ). The possible explanation for this finding is the specific mechanism of action of bortezomib.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our data supports the notion that hyperdiploidy retains its prognostic significance among patients with SRD. Peripheral blood absolute lymphocyte and monocyte counts have been used as surrogate markers of the tumour microenvironment and immune surveillance in several haematological malignancies, including multiple myeloma (Jimenez‐Zepeda et al , ; Dosani et al , ; Binder et al , ). Our data are consistent with these observations in newly diagnosed disease and abnormal lymphocyte counts remained of prognostic significance among patients with SRD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the increasing understanding of the connection between the immune system and tumor, immunotherapy is receiving increasing attention and the prognosis value of systemic immunerelated markers has been investigated in various tumors [5][6][7] . Because of the more convenient and affordable for detecting, absolute lymphocyte count (ALC) and monocyte count (AMC) in blood routine examination have been widely used for immune surveillance in several hematologic malignancies and solid tumors [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%